Comparison of Achilles Tendon Healing After Exposure to Combusted Tobacco, Vaping, and Control in a Rat Model. Issue 7 (29th July 2019) - Kennedy, Patrick; Saloky, Kaitlin; Yadavalli, Aditya; Barlow, Erin; Aynardi, Michael; Garner, Matthew; Bible, Jesse; Lewis, Greg; Dhawan, Aman
Objectives: The negative effects of smoking have been well documented following orthopedic injury. Though nicotine has been shown to be detrimental to musculoskeletal tissue healing, nicotine in the form of "Vaping" is being increasingly used as a perceived healthier alternative to actual smoking. It may theoretically obviate many of the harmful volatiles and chemicals contained within combusted tobacco that are additionally harmful to musculoskeletal healing, beyond just nicotine. The literature has yet to establish the benefits, or lack thereof, to exposure of e-cigarettes and their effect on tendon healing when compared to traditional combusted tobacco. Our objective was to evaluate the biomechanical and histological effects on Achilles tendon repair between inhaled combusted tobacco versus isolated nicotine exposure via vaping versus a control group in a small animal (Sprague Dawley Rat) model. Methods: 54 Sprague Dawley rats were randomly placed in a control, vaping, or cigarette cohort. Each group contained 17 rats for exposure and they were exposed six days per week. The smoking cohort was exposed to 2 unfiltered University of Kentucky research cigarettes in a smoking chamber (Image 1). The vaping group was exposed to e-cigarette vapor with equivalent nicotine exposure as compared to the cigarette group, over ten minutes at a flow rate of 2.4 L/min. The control group was placed in the smoking chamber with room air flowing through the chamber. All rats received their respective daily exposures for 4 weeks prior to surgery where transection and repair of the Achilles tendon was performed. Following surgery, the rats received 2 additional weeks of smoking vs vaping vs control exposure. After sacrifice, Achilles tendons were harvested and tested with tensile and a load to failure model (Image 2). Histological samples were sent for analysis. Results: Tensile load testing evaluated maximum force to rupture and tissue stiffness amongst the three cohorts. The control group demonstrated highest mean tensile strength of 41.0 N (18.3-55.1 N), with the cigarette cohort having the second highest mean tensile strength at 37.3 N (14.0-54.7 N), and finally the vaping group had the lowest at 32.28 N (17.8-45.1 N). One-way ANOVA with heterogeneous of variance was used for evaluation. There was a significant difference noted in load to failure when comparing controls to e-cigarettes (p=0.026). No statistical difference was seen between controls vs cigarettes (p=0.35). Histological analysis is in progress. Conclusion: Our investigation demonstrates that in a rat model, isolated nicotine exposure via "vaping" significantly impedes biomechanical healing properties of Achilles tendon surgical repair. Though smoking resulted in a lower maximum force to failure as compared to control, this difference was not significant. While E-cigarettes are often utilized as a perceived "safer" alternative to smoking combusted tobacco, this study suggests that use of e-cigarettes may be more detrimental to tendon healing than combusted tobacco in a rat Achilles model.